Comparison of Aneroid and Oscillometric Blood Pressure Measurements in Children. Issue 11 (20th September 2013) - Eliasdottir, Sigridur B.; Steinthorsdottir, Sandra D.; Indridason, Olafur S.; Palsson, Runolfur; Edvardsson, Vidar O.
Abstract : Limited data exist on the comparison of blood pressure (BP) measurements using aneroid and oscillometric devices. The purpose of the study was to investigate the difference in BP obtained using oscillometric and aneroid BP monitors in 9‐ to 10‐year‐old children. A total of 979 children were divided into group O, which underwent two oscillometric BP readings followed by two aneroid readings, and group A, which had BP measured in the reverse order. No significant difference was found between the mean (±standard deviation) of the two systolic BP readings obtained using the oscillometric and aneroid devices (111.5±8.6 vs 111.3±8.1 mm Hg; P =.39), whereas the mean diastolic BP was lower with the oscillometric monitor (61.5±8.0 vs 64.5±6.8 mm Hg; P <.001). A significant downward trend in BP was observed with each consecutive measurement, and agreement between the two monitors was limited. Multiple BP measurements are, therefore, recommended before the diagnosis of elevated BP or hypertension is made with either method.